Attributing human properties to computer artifacts: Developmental changes in children's understanding of the animate-inanimate distinction - A. Mikropoulos, Tassos; Misailidi, Ploussia; Bonoti, Fotini (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF